Antecedents of Customer Loyalty: An Empirical Analysis of Service Quality, Trust, and Satisfaction at Mixue Sungai Penuh - Rezki Agrisa Ditama; Bustami Bustami; Eka Putra; Azhar Azhar; Samsul Bahry Harahap (CV. Visionary Raya Sakti, 2026)
Purpose: This study aims to examine the antecedents of customer loyalty by analyzing the effects of service quality, trust, and customer satisfaction on customer loyalty at Mixue Sungai Penuh. The research seeks to develop an empirical model explaining how these key relational constructs contribute to strengthening long-term customer commitment in the food and beverage industry. Design/methodology/approach: This research employs a quantitative approach with a causal design. Data were collected through structured questionnaires distributed to 85 customers of Mixue Sungai Penuh using a purposive sampling technique. The measurement items were adapted from established scales in the marketing literature. Data were analyzed using multiple linear regression with IBM SPSS Statistics version 25 to test the direct effects of service quality, trust, and customer satisfaction on customer loyalty. Findings: The results reveal that service quality, trust, and customer satisfaction simultaneously have a significant effect on customer loyalty. Partially, service quality and trust significantly influence customer satisfaction, and customer satisfaction significantly affects customer loyalty. These findings indicate that customer satisfaction plays a crucial role in strengthening loyalty, while service quality and trust function as key drivers in shaping positive customer perceptions and behavioral intentions. Research implications: This study enriches the empirical literature on customer loyalty by confirming the importance of service quality, trust, and satisfaction in a local food and beverage retail context. Practically, the findings suggest that managers should prioritize consistent service performance and trust-building strategies to enhance customer satisfaction and ultimately foster loyalty. Future studies are encouraged to involve larger samples and additional variables to improve generalizability and theoretical development.